Using PRTR database for the assessment of surface water risk and improvement of monitoring in Japan. (7th February 2005) - Hartmann, Jens; Okada, Norio; Levy, Jason
In April 2003, the first PRTR (Pollutant Release and Transfer Register) was published in Japan. It is shown how the PRTR can be used to improve environmental risk assessment with the objective of reducing risk to ecosystem integrity and human health. By examining the superposition of all chemical releases into rivers, high levels of several contaminants are uncovered. Most of these chemicals have not been previously monitored. The outcome of the analysis helps to re-design existing environmental monitoring programmes and to identify these programmes.